2022
DOI: 10.1093/hr/uhab025
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection contributes to freezing tolerance as revealed by RNA-seq profiling ofRhododendronleaves during cold acclimation and deacclimation over time.

Abstract: Cold acclimation (CA) and deacclimation (DA), which are often accompanied by changes in freezing tolerance (FT), carbohydrates and hormones, are crucial for winter survival, especially under global warming. Plants with weak CA and premature DA caused by warm winters and/or unseasonal warm spells can be easily injured by adverse reactions to cold. Thus, understanding the molecular mechanisms of FT is imperative. In this study, we used high-throughput RNA-seq to profile the CA and DA of leaves of overwintering R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Although ELIPs have been found for so many years and proved to be photoprotective and low temperature‐sensitive (Liu et al, 2020, 2021; Noren et al, 2003; Wang et al, 2009; Wei et al, 2005), no research has yet looked into whether they directly contribute to plants' freezing tolerance. In this study, we demonstrated that RhELIP3 ‐OEs did show less freeze‐injury when compared with the WT after freezing treatment (Figure 3d,e), which could through protecting the PSII system due to the higher F v / F m , ΦII, qP, ETR and qL in RhELIP3 ‐OEs after 3‐day resumption (Figure 3f,g).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although ELIPs have been found for so many years and proved to be photoprotective and low temperature‐sensitive (Liu et al, 2020, 2021; Noren et al, 2003; Wang et al, 2009; Wei et al, 2005), no research has yet looked into whether they directly contribute to plants' freezing tolerance. In this study, we demonstrated that RhELIP3 ‐OEs did show less freeze‐injury when compared with the WT after freezing treatment (Figure 3d,e), which could through protecting the PSII system due to the higher F v / F m , ΦII, qP, ETR and qL in RhELIP3 ‐OEs after 3‐day resumption (Figure 3f,g).…”
Section: Discussionmentioning
confidence: 99%
“…We found that RhHY5 ‐OEs were more freezing tolerant than RhELIP3 ‐OEs, while the resumption of PSII‐related parameters of RhHY5 ‐OEs was not as good as RhELIP3 ‐OEs (Figures 3d,e and 5d,e), which suggests that the RhELIP3 ‐OEs improved the plants' freezing tolerance primarily through the pathway of photoprotection while RhHY5‐OEs did not. The upregulation of AtELIP1/2 in RhHY5‐OEs suggested that RhHY5 might partially participate in inducing the RhELIP3 expression, and the large amount of upregulation of AtELIP1/2 in the WT suggests that other low‐temperature sensing factors, such as CRY1, may also play a role in inducing the expressions of ELIPs (Liu et al, 2022). Thus, although RhHY5 could significantly induce the expressions of RhELIP3 or AtELIP1/2 , its capacity to induce the massive expressions of ELIPs under low temperatures might be limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…L., Pinus sylvestris , and Picea abies ( Joosen et al, 2006 ; Maestrini et al, 2009 ; Benedict et al, 2010 ; Vergara et al, 2022 ), and have addressed antioxidant enzymes ( Renaut et al, 2006 ) and TFs ( Vergara et al, 2022 ). Recently, researchers have paid more attention to the relationship between cold resistance and lignin and starch synthesis pathways ( Zhao et al, 2019 ; Liang et al, 2022 ; Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%